Developing and Validating a Questionnaire to Measure Some Factors of School Culture : A Psychometric Process - Iyer, Ramajanaki Doraiswamy (Prabandhan: Indian Journal of Management, 2017)
The purpose of this paper was to describe the process undertaken to evaluate the psychometric properties of a questionnaire developed to measure certain factors of school organization culture. Although various instruments are available to measure aspects of organization culture, instrument specific to measure school culture is limited. Factor analysis and construct validity tests (convergent validity and discriminant validity) were used to confirm the reliability and validity of the instrument. This study was non experimental, cross-sectional, and quantitative in nature. A questionnaire survey was conducted among 326 teachers in private and municipal schools in Mumbai. The response rate was 93%. Factor analysis of the 15 item instrument yielded a four-factor structure. The scale composite reliability values were found to be well above 0.7 and the average variance extracted values were also above the recommended value of 0.5. The study is an important contribution to the scarce research work in the field of school culture in India.